The Bone Collector - Noyce, Phillip; Washington, Denzel, 1954-; Jolie, Angelina, 1975-; Queen Latifah, 1970- (Burbank, CA : Universal Studios Home Entertainment, 2000)
When a serial killer begins committing gruesome murders and leaving bizarre clues behind, a recently paralyzed homicide detective must team up with a rookie cop in order to catch him.
Originally released as a motion picture in 1999.
Dolby digital 5.1, wide screen 2.35:1.
Features: Spotlight on location; feature commentary with director Phillip Noyce; production notes, cast and filmmakers; theatrical trailer; Universal showcase; DVD-ROM features.
Denzel Washington, Angelina Jolie, Queen Latifah, Michael Rooker, Mike McGlone.
MPAA rating: R.
In English or French.
Keywords: People with disabilities -- Drama; Serial murder investigation -- Drama; Serial murderers -- Drama; Detective and mystery films; Fiction films; Video recordings for the hearing impaired; Feature films; Detective films; Mystery films